Remote treatment of sleep‐related trichotillomania and trichophagia. Issue 2 (21st February 2018) - Lichtblau, Katherine R.; Romani, Patrick W.; Greer, Brian D.; Fisher, Wayne W.; Bragdon, Allie K.
Abstract : We used a biobehavioral treatment consisting of melatonin and a standardized bed and wake time to decrease one girl's head and mouth touches associated with sleep‐related trichotillomania and trichophagia. We remotely coached the girl's caregiver to implement all procedures and monitored response to treatment using a DropCam Pro video camera equipped with night‐vision capabilities. Head and mouth touches decreased, and her sleep pattern improved with the combination of treatment strategies. We discuss our use of a novel mode of service delivery to treat sleep‐related problem behavior.